Model Fuzzy MADM in The Decision Support System of Mustahik Service Program Beneficiaries at Laznas PPPA Daarul Quran Center Tangerang - Lukman Nulhakim; Doni Andriansyah; Firda Devia Putri (IAIC Publishing, 2020)
Charity is one of the good deeds taught in Islam. Doing charity is giving out or donating a piece of the property or money to someone else. The amil institution is one of the places where they receive donations and distribute them to those who are entitled. One of the amil institutions is Laznas PPPA Daarul Quran that has a mustahik service program where they must be focused on providing educational, health, venture capital, or other aid to mustahik. The problem we found is that mustahik selection is still conducted by hand, resulting in the lack of accuracy of mustahik. There are eight criteria in determining the mustahik; fardhu prayer, family income, reading Al-Quran, sunnah prayer, social activities, number of loads, residence, and marital status. The purpose of this research is to build a decision support system to facilitate the management and distribution of aid to make it more targeted. The method used in this research is Simple Additive Weighting or SAW with a model Fuzzy Multi-Attribute Decision Making or FMADM. The method is selected because it can choose the best alternative by calculating and weighting the weight value of any criteria, and then proceed to determining the mustahik and giving help based on the number of funds available.